Social and Economic Transformation of Women through Microfinance: Lessons from the M. Yunus Economic Movement - Siti Aisyah; Almuzayyad (Pustaka Peradaban, 2024)
Women's economic empowerment has become a central issue in global development, reflecting the need for gender equality and social justice. Microfinance institutions (MFIs), particularly Grameen Bank, have played a crucial role in providing financial access to previously underserved women. MFIs have proven that providing financial access to women not only increases their income but also changes power dynamics within households and communities. Despite significant progress, there are still challenges to overcome, including the risk of domestic violence, fraud, and dependence on patriarchal norms. Some recommendations provided in this paper include enhancing awareness training on fraud and financial skills, as well as developing comprehensive social performance measurement criteria. By addressing these challenges, microcredit programs and other MFIs are expected to become more effective instruments in helping women achieve greater economic empowerment and promoting inclusive and sustainable economic growth. Pemberdayaan ekonomi perempuan telah menjadi isu sentral dalam pembangunan global sekaligus mencerminkan kebutuhan akan kesetaraan gender dan keadilan sosial. Lembaga keuangan mikro (MFIs), terutama Grameen Bank, memainkan peran penting dalam memberikan akses keuangan kepada perempuan yang sebelumnya tidak terlayani. MFIs telah membuktikan bahwa memberikan akses keuangan kepada perempuan tidak hanya meningkatkan pendapatan mereka, tetapi juga mengubah dinamika kekuasaan di dalam rumah tangga dan komunitas. Meskipun telah ada kemajuan signifikan, masih ada tantangan yang perlu diatasi, termasuk risiko kekerasan domestik, penipuan, dan ketergantungan pada norma patriarki. Beberapa rekomendasi yang diberikan dalam tulisan ini meliputi peningkatan pelatihan kesadaran terhadap penipuan dan keterampilan keuangan, serta pengembangan kriteria pengukuran kinerja sosial yang komprehensif. Dengan mengatasi tantangan ini, diharapkan program mikrokredit dan MFIs lainnya dapat menjadi instrumen yang lebih efektif dalam membantu perempuan mencapai pemberdayaan ekonomi yang lebih besar, serta mendorong pertumbuhan ekonomi yang inklusif dan berkelanjutan.